1996
DOI: 10.2134/agronj1996.00021962008800050011x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Design Factors Affecting Error Variation in Orchardgrass

Abstract: Several experimental design factors over which the researcher has control may affect the precision of field experiments. The objective of this experiment was to identify the effects of changing plot size, incomplete block size, and incomplete block shape on precision of forage yield and quality estimates in orchardgrass (Dactylis glomerata L.). Orchardgrass seed was planted uniformly into 288 plots of various sizes. Forage yield, in vitro dry matter digestibility (IVDMD), and neutral‐detergent fiber (NDF) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Thus, spatial variation appeared to be due to field heterogeneity per se, and was not affected by variation in alley position between rows of plots. This is consistent with observations of Casler and Tageldin (1996), who showed that variation in alley position or marking was important for 1.4-m 2 plots, but not for plot sizes of 2.8 m 2 or greater. Lin and Binns (1986) described working rules for improving the precision of future RCB designed trials, using blocking information from prior RCB designed trials.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, spatial variation appeared to be due to field heterogeneity per se, and was not affected by variation in alley position between rows of plots. This is consistent with observations of Casler and Tageldin (1996), who showed that variation in alley position or marking was important for 1.4-m 2 plots, but not for plot sizes of 2.8 m 2 or greater. Lin and Binns (1986) described working rules for improving the precision of future RCB designed trials, using blocking information from prior RCB designed trials.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, no method of spatial analysis attempted in this study was effective at decreasing ?-values of these trials. Spatial adjustments should be less effective for small blocks, because the probability of significant spatial variation is substantially reduced compared with large blocks (Briggs and Shebeski, 1968;Casler and Tageldin, 1996;Warren and Mendez, 1982). These three trials were excluded from all analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Phenotypic selection based on spaced‐plant evaluations is used in forage breeding to access the within‐family genetic variability and it increases the accuracy and genetic gain as shown here. However, selection experiments in perennial grasses and legumes have shown that genetic correlations between some traits, for example, biomass yield, evaluated in spaced plantings and sward plots ranges from negative to positive values, depending on species and target trait (Casler and Tageldin, 1996; Annicchiarico, 2006; Casler, 2008; Casler and Brummer, 2008; Wilkins and Humphreys, 2003). The optimal choice of selection methods was independent of whether selection was based directly on the target trait y or indirectly on trait x , relying on correlated responses to achieve gains in trait y .…”
Section: Discussionmentioning
confidence: 99%
“…The experimental design was a sets‐in‐replicates design (Schutz and Cockerham, 1966) with 50 sets for orchardgrass and smooth bromegrass or 60 for hybrid wheatgrass, seven polycross families per set, and two replicates. Set size was determined partly by data from an orchardgrass uniformity trial (Casler and Tageldin, 1996) and partly by previous experiences with block sizes ranging from 4 to 35 in numerous cultivar tests. Each set contained polycross families from only one population.…”
Section: Methodsmentioning
confidence: 99%